Auras localized to the temporal lobe disrupt verbal memory and learning — Causal evidence from direct electrical stimulation of the hippocampus - Diana Pizarro; Emilia Toth; Auriana Irannejad; Kristen O. Riley; Zeenat Jaisani; Wolfgang Muhlhofer; Roy Martin; Sandipan Pati (Epilepsy and Behavior Case Reports, 2018)
Auras (focal aware seizure; FAS) are subjective ictal events with retained consciousness. Epileptiform activities can disrupt cognitive tasks, but studies are limited to seizures with impaired awareness. As a proof of concept, we examined the cognitive effects of direct electrical stimulation to the left hippocampus which induced a habitual FAS in a patient with left mesial temporal lobe epilepsy. During the induced habitual FAS, verbal memory performance declined significantly as compared to pre-stimulation testing. Tasks measuring auditory working memory and psychomotor processing speed were not affected by the stimulation. The study confirms that FAS can impair episodic verbal memory and learning. Keywords: Verbal memory, Aura, Focal aware seizure, Learning, Hippocampus, Epilepsy